A laser doppler anemometer for fine scale measurements of turbulence - Tian, Yujia (2019)
Research on turbulence has been ongoing for more than a century and yet, it is still considered as a topic worth more investigating due to its complex nature. In particular, the issue with self-similarity is still under debate. With more advanced equipment and processing techniques, this project focuses on self-similarity of the flow from a round turbulent jet, particularly in the scaling factors derived from the spatial turbulent kinetic energy spectra at different downstream positions along the jet centreline. Two separate sets of Laser Doppler Anemometer (LDA) measurements were conducted and the range of downstream distance measured covers from 10 jet diameter (d) up to 92.8d. The Reynolds numbers for the two measurements were 20500 and 19800 respectively based on the nozzle exit velocity and diameter. Unlike the commercial system where information such as velocity, particle arrival time and residence time are obtained directly, equidistantly sampled voltages were acquired and post-processed with a transparent and flexible programme. Parameters obtained such as the mean velocity and turbulent velocity were found to agree with literature values. Both the temporal and spatial spectra were computed. The data obtained were normalised using the local mean velocity square and cross-checked with Kolmogorov’s -5/3 power law. The spatial spectra were scaled and found to collapse nicely, forming a single normalised curve. The scaling factors were plotted against the downstream distance. A linear relationship, at least within the fully developed region, was found between them. However, a better linear fit was found for the whole range measured, including the developing region. The position of the ‘virtual origin’ for the scaling behaviour was obtained by extrapolating the linear fit and finding the intercept with the horizontal axis. With the findings of this project, further studies may be conducted to reveal more about the turbulence structure and energy transfer in both the developing and the fully developed region of a jet, hence better predicting its turbulence behaviour in the future.